2021
DOI: 10.1088/1755-1315/914/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal properties of orchidaceae by local communities in Lake Toba region, North Sumatra, Indonesia

Abstract: Orchids are plant species with beauty and medicinal purposes, but, limited exploration has been conducted on potential utilization of Orchidaceae for medicinal purposes. This study aims to describe the local wisdom in utilization of Orchidaceae in traditional medicine and to identify the phyto-chemical content in particular orchid species which utilized for herbal medicine by local communities in the Lake Toba region. The study was conducted through exploration and in-depth interviews with 24 local communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Ethnobotanical information collected by means of interviews and questionnaires among the traditional community healers revealed that A. rigida leaf is popular among the Santhal community and has a number of beneficial effects as mentioned in Table 1. It was reported that the juice (boiled) of A. rigida is effective as tonic to strengthen body when taken orally on daily basis among the Lake Toba community, Indonesia which is in compliance with those of the Santhal community traditional healers, though the processing and dose is different (9). Similarly, the ethnomedicinal use of the whole plant of A. rigida was documented in Thailand as body tonic (21).…”
Section: Ethnobotanical Surveymentioning
confidence: 94%
See 1 more Smart Citation
“…Ethnobotanical information collected by means of interviews and questionnaires among the traditional community healers revealed that A. rigida leaf is popular among the Santhal community and has a number of beneficial effects as mentioned in Table 1. It was reported that the juice (boiled) of A. rigida is effective as tonic to strengthen body when taken orally on daily basis among the Lake Toba community, Indonesia which is in compliance with those of the Santhal community traditional healers, though the processing and dose is different (9). Similarly, the ethnomedicinal use of the whole plant of A. rigida was documented in Thailand as body tonic (21).…”
Section: Ethnobotanical Surveymentioning
confidence: 94%
“…Apart from being an ornamental plant, A. rigida is used amongst a group of people residing around the globe for its medicinal values. The Bataknese tribe residing in Indonesia uses the decoction of A. rigida whole plant as a tonic to strengthen body (9). Similarly, the leaf and root are reported to stimulate blood circulation and relief from joint and muscular pain (10).…”
Section: Introductionmentioning
confidence: 99%
“…Toba (Aswandi and Kholibrina, 2021), Papua (Utami et al, 2017), and middle Java (Nugroho et al, 2016). Some orchid species from the genus Liparis have been used in traditional Chinese for the treatment of anti-inflammatory, antibacterial activities, and hemostasis (Liang et al, 2019).…”
Section: Phytochemistry Profilementioning
confidence: 99%
“…Liparis nervosa belongs to the Orchidaceae family and is found in many parts of China. It is used in traditional herbal medicine for skin inflammation, swelling, and the detoxification of snake venom [105]. Chen et al [17] conducted a study on the antitumor effect of PAs isolated from L. nervosa on HCT116 human colorectal cancer cells.…”
Section: Anticancer Propertiesmentioning
confidence: 99%